Penerapan Guided Imagery untuk Penurunan Tingkat Kecemasan pada Pasien Ulkus Diabetik - Nugrahaeni, Tias Dwi; Hidayah, Nurul; Margono, Margono (Borobudur Nursing Review, 2023)
Diabetes Mellitus is a disease characterized by blood glucose levels that exceed normal (hyperglycemia) due to the body's lack of insulin, both absolute and relative. Diabetes Mellitus has complications that occur in patients, such as diabetic ulcers which will affect the patient's quality of life. The presence of diabetic ulcers is considered to be the main cause of amputation of the lower extremities in Diabetes Mellitus patients. This condition can cause Diabetes Mellitus patients to have anxiety about the disease they are suffering from. Anxiety arising from diabetic ulcers can be treated nonpharmacologically by guided imagery. Guided imagery relaxation is a method that can be used to reduce anxiety by imagining a state or a series of pleasant experiences in a guided manner by involving the senses. The purpose of the case study was to compile a resume of nursing care for diabetic ulcer patients and to identify the application of guided imagery to reduce anxiety levels in diabetic ulcer patients. The method used is descriptive research with a case study design through the nursing care process, namely assessment, nursing diagnosis, intervention, implementation, and evaluation. Data collection techniques by observation, interviews, and documentation. This case study instrument uses a nursing assessment format, Hamilton Rating Scale for Anxiety (HARS) assessment format, a nursing kit, and a blood glucose level checking tool. The results of the application of guided imagery were given to 2 (two) diabetic ulcer patients who were carried out for 15 minutes within 1 week with 3 times the application of guided imagery. It was found that anxiety could be resolved. In conclusion, the application of guided imagery is useful for dealing with anxiety in diabetic ulcer patients.